Industrial subsidy policy and the optimal level of specialization - Dubey, Ram Sewak (2022)
Despite compelling rationale based on the theory of comparative advantage for free trade, many countries adopt restrictive trade practices. In this paper we investigate this puzzle in a stylized two-country two-good Ricardian model of international trade. Governments can offer protection to domestic industries via industrial subsidy policy in this model. We prove the existence of a Nash equilibrium in the two-player game where industries choose the level of specialization. We determine the necessary conditions for complete specialization in (a) the free-trade regime; and (b) the protectionist regime implemented through industrial subsidy policy. Our results show that if the government intends to promote complete specialization, then a high degree of comparative advantage and a large elasticity of substitution between export and import goods are required. Empirical evidence on these two parameters indicate that complete specialization is unlikely to survive in the protectionist regime.